Studies of Proton-Ligand and Metal-Ligand Stability Constants of Cu(II) and Ni(II) Complexes of Substituted 1,3-Thiazines - Dighade, S.R.; Narwade, M.L.; Chincholkar, M.M. (Asian Journal of Chemistry, 2010)
The interactions of Cu(II) and Ni(II) metal ions with (i) 4-(2- hydroxy-5-methylphenyl)-5-benzoyl-6-(2'-furyl)-2-imino-6H-2,3- dihydro-1,3-thiazine (L1). (ii) 4-(2-Hydroxy-5-methylphenyl)-6-(4- methoxyphenyl)-2-imino-6H-2,3-dihydro-1,3-thiazine (L2) have been studied at 0.1 M ionic strength. It is observed that and Cu(II) and Ni(II) metal ions form 1 : 1 and 1 : 2 complexes with L1 and L2. The substituted 1,3-thiazines show formation of stepwise complexes. The order of proton-ligand stability constant is as pKL1 > pKL2 . The data obtained for pK and log K are used (i) to see the effect of substitutents, (ii) to check the validity of log K = a pK + b. Here proton-ligand and metal-ligand stability constants have been studied pH-metrically by Calvin-Bjerrum titration technique.